Scattering of electromagnetic waves by a perfectly conducting cylinder with a thin lossy magnetic coating. - Strifors, H.C (IEEE Transactions on antennas and propagation)
We study the scattering interaction of electromagnetic (EM) waves with an infinite cylinder coated with a lossy dielectric material with frequency-dependent material properties. These properties are hypothetical, yet representative of a wide class of available materials. The monostatic and bistatic scattered widths (SW) are evaluated for the TM or TE polarization cases. These calculations require the use of algorithms to evaluate Bessel-Hankel functions of complex arguments. These algorithms are based on a continued fraction approach, which ensures stability of the recursion relations. The bistatic plots of the TM and TE scattering widths for the coated body are displayed in a convenient color-graded scale. The reductions in the scattering widths produced by this type of coating are determined in selected frequency bands and angular sectors, in both polarization cases. It is quantitatively shown how curvature and polarization shift the effectiveness band of the coating. The determined regions in which the SW are minimally affected are the most suitable for target identification purposes